Isu Hukum Lingkungan Internasional Mengenai Gerakan Ecofeminisme Di Afrika - Putri Difa Zhafirah (Consensus : Jurnal Ilmu Hukum, 2024)
Ecofeminism is a movement about the relationship between the exploitation and degradation of nature and the subordination and oppression of women. One of these movements began with global environmental issues that occurred in the Lake Chad region, in Africa. Where the lake borders Chad, Nigeria, Niger, and Cameroon. So, the four countries are really affected, along with the countries that are connected to them. In the Lake Chad region, it is there that women have to travel long distances to get water for their basic needs. But in the midst of their work in traveling long distances to Lake Chad, they were sexually assaulted. This can affect their right to education because they have to drop out of school to meet the needs of their families. All of these issues are related to women's rights in environmental instability. Therefore, the ecofeminist movement approach is very necessary, along with effective environmental law in addressing the issue.